2014
DOI: 10.4067/s0718-95162014005000056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liquid humus and calcium sulphate on soil aggregation

Abstract: An Ultic Haploxeralf soil collected from ridges built into the slopes of the Coastal Mountain Range of Central Chile was used in applications of humic and fulvic acids (HFA) extracted from sludge from sewage treatment plants, in combination with gypsum (CaSO 4 ). A total of 12 treatments were applied by combining four doses of HFA (0, 20, 30 and 40 t ha -1 ) with three doses of gypsum (0, 1.2 and 6.0 t ha -1 ). The effect of these treatments was assessed using three indicators of the degree of soil aggregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
0
12
2
1
Order By: Relevance
“…In addition, the weak aggregation response shown by CaCO 3 is also similar to that reported by Chan and Heenan (1998), who observed a change in the structural stability of the soil only three years after the application of CaCO 3 . However, our results contrast with those reported by Baldock et al (1994) and Norambuena et al (2014). Specifically, both studies reported a significant increase in aggregate stability when simultaneously applying organic matter, CaSO 4 and CaCO 3 (Baldock et al, 1994) and when applying liquid humus with CaSO 4 (Norambuena et al, 2014).…”
Section: Effect Of Ca(oh) 2 On Soil Aggregationcontrasting
confidence: 99%
See 4 more Smart Citations
“…In addition, the weak aggregation response shown by CaCO 3 is also similar to that reported by Chan and Heenan (1998), who observed a change in the structural stability of the soil only three years after the application of CaCO 3 . However, our results contrast with those reported by Baldock et al (1994) and Norambuena et al (2014). Specifically, both studies reported a significant increase in aggregate stability when simultaneously applying organic matter, CaSO 4 and CaCO 3 (Baldock et al, 1994) and when applying liquid humus with CaSO 4 (Norambuena et al, 2014).…”
Section: Effect Of Ca(oh) 2 On Soil Aggregationcontrasting
confidence: 99%
“…However, our results contrast with those reported by Baldock et al (1994) and Norambuena et al (2014). Specifically, both studies reported a significant increase in aggregate stability when simultaneously applying organic matter, CaSO 4 and CaCO 3 (Baldock et al, 1994) and when applying liquid humus with CaSO 4 (Norambuena et al, 2014).…”
Section: Effect Of Ca(oh) 2 On Soil Aggregationcontrasting
confidence: 99%
See 3 more Smart Citations